Bat flies (Diptera: Nycteribiidae and Streblidae) infesting cave-dwelling bats in Gabon: diversity, dynamics and potential role in Polychromophilus melanipherus transmission. Issue 1 (December 2016) - Obame-Nkoghe, Judicaël; Rahola, Nil; Bourgarel, Mathieu; Yangari, Patrick; Prugnolle, Franck; Maganga, Gael; Leroy, Eric-Maurice; Fontenille, Didier; Ayala, Diego; Paupy, Christophe
Abstract Background Evidence of haemosporidian infections in bats and bat flies has motivated a growing interest in characterizing their transmission cycles. In Gabon (Central Africa), many caves house massive colonies of bats that are known hosts ofPolychromophilus Dionisi parasites, presumably transmitted by blood-sucking bat flies. However, the role of bat flies in bat malaria transmission remains under-documented. Methods An entomological survey was carried out in four caves in Gabon to investigate bat fly diversity, infestation rates and host preferences and to determine their role inPolychromophilus parasite transmission. Bat flies were sampled for 2–4 consecutive nights each month from February to April 2011 (Faucon and Zadie caves) and from May 2012 to April 2013 (Kessipoughou and Djibilong caves). Bat flies isolated from the fur of each captured bat were morphologically identified and screened for infection by haemosporidian parasites using primers targeting the mitochondrial cytochrome b gene. Results Among the 1, 154 bats captured and identified asMiniopterus inflatus Thomas (n  = 354), Hipposideros caffer Sundevall complex (n  = 285), Hipposideros gigas Wagner (n  = 317), Rousettus aegyptiacus Geoffroy (n  = 157, andColeura afra Peters (n  = 41), 439 (38.0 %) were infested by bat flies. The 1, 063 bat flies recovered from bats belonged to five taxa:Nycteribia schmidlii scotti Falcoz, Eucampsipoda africana Theodor, Penicillidia fulvida Bigot, Brachytarsina allaudi Falcoz andRaymondia huberi Frauenfeld group. The mean infestation rate varied significantly according to the bat species (ANOVA, F (4, 75) = 13.15, P  < 0.001) and a strong association effect between bat fly species and host bat species was observed.Polychromophilus melanipherus Dionisi was mainly detected inN. s. scotti andP. fulvida and less frequently inE. africana, R. huberi group andB. allaudi bat flies. These results suggest thatN. s. scotti andP. fulvida could potentially be involved inP. melanipherus transmission among cave-dwelling bats. Sequence analysis revealed eight haplotypes ofP. melanipherus . Conclusions This work represents the first documented record of the cave-dwelling bat fly fauna in Gabon and significantly contributes to our understanding of bat fly host-feeding behavior and their respective roles inPolychromophilus transmission.